A Review of Fiber Optofluidic Microlasers: Structures, Characteristics, and Applications (Laser Photonics Rev. 16(1)/2022). Issue 1 (7th January 2022) - Yang, Xi; Gong, Chaoyang; Zhang, Chenlin; Wang, Yanqiong; Yan, Guo‐Feng; Wei, Lei; Chen, Yu‐Cheng; Rao, Yun‐Jiang; Gong, Yuan
Abstract : Fiber Optofluidic Microlasers Fiber optofluidic laser (FOFL) is one of the multidisciplinary frontiers that has a deep rooting in the fields of lasers, optical fibers, and microfluidics. In article number 2100171, Xi Yang, Chaoyang Gong, Chenlin Zhang, Yuan Gong, and co‐workers focus on the recent advances in FOFLs and highlight the uniqueness of optical fiber for lasing and sensing. Typical biochemical applications and challenges of FOFLs are also given.